Tracing the footsteps of a world anthropologist: clues and hypotheses for a biography of John V. Murra (Isaak Lipschitz) - Anăstăsoaie , Marian Viorel (2023)
This article addresses the relationship between personal identity, political commitment and scholarship in the biography of anthropologist John Victor Murra (Isaak Lipschitz). Born in 1916 into a Russian‑Jewish family in Odessa, he grew up, studied and became involved in Communist politics in Romania before his departure for Chicago in 1934. His 1956 Ph.D. thesis at University of Chicago on the Inca state helped Murra to become an influential figure in the field of Andean anthropology. Based on archival work and several testimonies, this article traces the influence of his upbringing and political commitment on his academic career.